The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s13312-016-0786-3
|View full text |Cite
|
Sign up to set email alerts
|

Oromotor stimulation for transition from gavage to full oral feeding in preterm neonates: A Randomized controlled trial

Abstract: Oromotor stimulation along with routine care reduces the duration of gavage feeding in preterm neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
4
23
0
6
Order By: Relevance
“…On the other hand, our results concerning food autonomy are not consistent with most of the literature. Numerous studies suggested that the duration between the transition from enteral feeding to autonomous oral feeding was reduced through oral stimulation [17][18][19][20][21][22]. Our study showed a greater quantity of milk ingested during the rst feeding which remained within the limits of signi cance.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, our results concerning food autonomy are not consistent with most of the literature. Numerous studies suggested that the duration between the transition from enteral feeding to autonomous oral feeding was reduced through oral stimulation [17][18][19][20][21][22]. Our study showed a greater quantity of milk ingested during the rst feeding which remained within the limits of signi cance.…”
Section: Discussionsupporting
confidence: 56%
“…On the one hand, the main ones have been length of hospital stay, [36,38,43,44,46] transition time from tube feeding to independent feeding, [36,38,39,43,44,46] sucking skills, [37,40,42,45] oral feeding skills, [37,39,42,44] motor function [38,43] and growth [37,38,43]. On the other hand, some of them considered assessing the influence on breastfeeding skills, [46] infants' alertness [37] and their physiological constants [37].…”
Section: Discussionmentioning
confidence: 99%
“…[8] A study conducted by Bala P, Kaur R, Mukhopadhyay K et al revealed that non-nutritive sucking for 5 to 10 minutes before oral feeds appears to improve feeding performance, physiological stability during feeds and volume consumed during feeds. [9] They concluded that Premature Infant Oral Motor Intervention (PIOMI) found as a useful method for preterm neonates and PIOMI should be integrated in feeding rehabilitation programs of the preterm neonates born with gestational age of 26-29 weeks. [10] Oromotor stimulation found to be effective in improving the sucking frequency, latch scores and fastens the transition time from spoon feeding to breast feeding.…”
Section: Introductionmentioning
confidence: 99%